Zagadnienie reformy polskiego systemu podatkowego - Gomułowicz, Andrzej (Wydział Prawa i Administracji UAM, 1989)
The Polish tax system reform is to consist — according to initial proposals presented by the government — in adopting two main types of taxation, i.e. initial taxation — in the form of value added tax;, and final taxation — in the form of common income tax. Besides, one cannot exclude other supplementary forms of taxation (local, property and agricultural taxes). The reconstruction of the tax system must not be limited to a narrowly understood financial sphere. On the contrary, it must correspond with the overall conception of development of market mechanisms in Polish economy. It is the starting point, the most important condition of rationalizing economic and social relations. As long as the above condition is not met, the tax system reform will be of isolated character and thus devoid of sense. It seems that the future tax system should in the first place perform income functions. Thus, it would mean that the tax system would evolve towards the tax neutrality conception and that interventionist and stimulative functions would be abondoned. Extra-fiscal functions are the consequence of the centralized control over economic processes exercised by the State. If the market economy system were implemented in Poland, tax interventionism should give way to the principle of tax neutrality. Neutrality of taxation should find its expression in legal construction of the future tax system. Taxes must not hinder the economic development, and must not lead to the elimination or reduction of sources of taxes. They must not make taxpayers give up their economic activity, nor must they weaken the economic potential of taxpayers or lead to their pauperization. In short, the reformers should aim at creating a so-called good and modern tax system in Poland.
Problems of the Polish tax system reform